A novel Mariannaea species isolated from decayed pine needles in Japan - Watanabe, Kohei; Hirose, Dai (Phytotaxa, 2021)
A strain of the fungal genus Mariannaea, isolated from decayed leaves of Japanese red pine (Pinus densiflora), was identified to be a new species based on its molecular phylogeny and morphology. Molecular phylogenetic analysis revealed that the fungus belongs to a clade containing M. punicea and related species (M. punicea-related species) and that it forms a lineage independent of these species. Microscopic morphological comparisons with M. punicea-related species indicated that the new isolate differs with respect to the width of the phialides and length of the conidiophores. Comparison of macroscopic morphological characteristics revealed that M. punicea-related species are characterized by reddish-purple colonies, whereas the new isolate lacks this distinctive pigmentation. Moreover, the surface structure of the colonies of this fungus has a distinct irregular undulate pattern toward the margins. Given that this isolate can be clearly distinguished from the known M. punicea-related species, we consider the fungus to be a newly identified species, for which we propose the name Mariannaea imbricata sp. nov.